Drug therapy problems and associated factors among adult patients admitted to the surgical ward in a resource-limited setting - Seid, Taju; Abdela, Jemal; Dechasa, Mesay; Nigussie, Shambel (Frontiers in Pharmacology, 2025)
BackgroundDrug therapy problems are common in hospitalized patients and may lead to increased hospital stays, healthcare costs, and increased risk of morbidity and mortality. Despite these facts, limited data exist on the magnitude of DTPs and associated factors among adult surgical patients in resource-limited settings, particularly in a current study setting. Therefore, this study aimed to assess the magnitude of DTPs and associated factors among adult surgical patients at study setting in Ethiopia.MethodsA hospital-based cross-sectional study was conducted at Wachemo University Comprehensive Specialized Hospital from January 1 to 30 March 2024. Data were collected through patients’ interviews and chart reviews using pre-tested questionnaires and data abstraction formats. Data were analyzed using Statistical Package for Social Science version 20. Factors associated with drug therapy problems were determined by binary logistic regression analysis. A p-value of less than or equal to 0.05 was considered statistically significant in the final analysis, and an adjusted odds ratio with a 95% confidence interval was used to determine the strength of the association.ResultsThe total number of recruited patients was 330. Of them, 304 participants who fulfilled the inclusion criteria. Of those participants, 216 (71.1%) were males. The mean age of the study participants was 44 (±17) years. Nearly half of the patients encountered at least one drug therapy problem, and 464 drug therapy problems were identified with a magnitude of 73.68% (95% CI: 0.684–0.785). Non-compliance (27.0%) was the most frequently identified drug therapy problem, followed by a need for additional drug therapy (21.1%). Length of hospital stay ≥7 days [adjusted odds ratio (AOR) = 2.47 [95% confidence interval (CI) 1.243–4.909, p = 0.01]), ≥5 drugs taken per day (AOR = 2.874 [95%CI: 1.411–5.851, p = 0.004]), and postoperative antibiotic use (AOR = 0.057 [95%CI: [0.028–0.115, p = 0.001]) significantly affect drug therapy problems.ConclusionThis study identified a high prevalence of DTPs that was independently predicted by the presence of polypharmacy, prolonged hospital stay (≥7 days), and postoperative antibiotic use. Non-compliance were the most frequent identified drug therapy problems. Therefore, early identification of drug therapy problems and the associated factors may enhance the prevention and management of drug therapy problems.